2016
DOI: 10.1016/j.celrep.2015.12.066
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the Cortical Subventricular Zone Requires MDGA1-Mediated Aggregation of Basal Progenitors

Abstract: The subventricular zone (SVZ) provides a specialized neurogenic microenvironment for proliferation and aggregation of basal progenitors (BPs). Our study reveals a mechanism for the aggregation of BPs within the SVZ required for their proliferation and generation of cortical layer neurons. The Autism-related IgCAM, MDGA1 is locally expressed in the BP cell membrane where it co-localizes and complexes with the gap junction protein Connexin43. To address MDGA1 function, we created a floxed allele of MDGA1 and del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The Ig domains 4–6 are reported to play a role in determining synaptic localization of MDGA1 and MDGA2 ( Loh et al., 2016 ). Adhesive interactions of MDGA with as-yet-unidentified partners may be responsible for the MDGA-dependent aggregation of basal progenitor cells in the subventricular zone ( Perez-Garcia and O’Leary, 2016 ), radial migration of cortical neurons ( Takeuchi and O’Leary, 2006 ), and directed axon outgrowth ( Ingold et al., 2015 , Joset et al., 2011 ). The widespread expression of NLs ( Varoqueaux et al., 2006 ) and NRXs ( Brown et al., 2011 , Górecki et al., 1999 ) from early postnatal ages also raises the interesting possibility that MDGAs may function to shield NLs at the stage of process outgrowth to prevent premature axon-dendrite adhesion and synaptogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The Ig domains 4–6 are reported to play a role in determining synaptic localization of MDGA1 and MDGA2 ( Loh et al., 2016 ). Adhesive interactions of MDGA with as-yet-unidentified partners may be responsible for the MDGA-dependent aggregation of basal progenitor cells in the subventricular zone ( Perez-Garcia and O’Leary, 2016 ), radial migration of cortical neurons ( Takeuchi and O’Leary, 2006 ), and directed axon outgrowth ( Ingold et al., 2015 , Joset et al., 2011 ). The widespread expression of NLs ( Varoqueaux et al., 2006 ) and NRXs ( Brown et al., 2011 , Górecki et al., 1999 ) from early postnatal ages also raises the interesting possibility that MDGAs may function to shield NLs at the stage of process outgrowth to prevent premature axon-dendrite adhesion and synaptogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Mdga2 heterozygous mice were viable and fertile on a C57BL6 background, with no obvious defects in gross brain morphology into adulthood. Previous data suggested roles for MDGAs in cortical lamination (Ishikawa et al, 2011;Perez-Garcia and O'Leary, 2016;Takeuchi and O'Leary, 2006). Thus, we assessed cortical morphology using Nissl stain and layer-specific markers Cux2 and Er81 but observed no obvious deficits in adult Mdga2 +/À mice (Figure S2E).…”
Section: Mdga2 Is Highly Expressed In Neocortex and Hippocampus And Knockout Is Lethalmentioning
confidence: 71%
“…Neurodevelopmental genes are indeed an important factor to take into consideration since functional and anatomical insults associated to defects in these genes during brain development can trigger the appearance of ASDs in the childhood. Genome-wide association studies have identified susceptibility genes for ASDs such as forkhead box p2 (FOXP2) ( Toma et al, 2013 ) or the MAM domain containing glycosylphosphatidylinositol anchor (MDGA) genes ( Bucan et al, 2009 ; Pettem et al, 2013 ; Perez-Garcia and O’Leary, 2016 ) and have provided evidence supporting the idea that the large numbers of variants associated with ASDs converge toward a core set of dysregulated biological processes ( Murdoch and State, 2013 ). The genes that have been linked to ASDs can be grouped into three broad categories: those involved in synapse structure and activity ( Etherton et al, 2011a , b ; Peca and Feng, 2012 ), those involved in protein synthesis ( Kelleher and Bear, 2008 ), and those involved in regulating gene expression ( van Bokhoven, 2011 ).…”
Section: Introductionmentioning
confidence: 99%